The Norton anthology of poetry - Ferguson, Margaret W.; Salter, Mary Jo; Stallworthy, Jon (W.W. Norton, 1996)
Over three editions, The Norton Anthology of Poetry has become the classroom standard for the study of poetry in English. A wide and deep quarry of poems from the medieval period to the present, it is a book instructors rely on as a uniquely flexible teaching anthology, and one that students delve into well beyond college.